Analysis of Best Intrusion Detection System Software Selection for Cloud Infrastructure Using the Analytical Hierarchy Process (AHP) Method - Rifanni Nurdin; Putri Harahap; Lela Budiarti (Journal of Information System and Education Development, 2026)
Selecting the right security software is a critical decision for cloud infrastructure managers. This research aims to determine the best Intrusion Detection System (IDS) software using the Analytical Hierarchy Process (AHP) method. The evaluation process involves several key criteria, such as detection accuracy, resource consumption, ease of implementation, and cost. Several IDS alternatives, including Snort, Suricata, and Zeek, were compared through pairwise comparisons to obtain a priority ranking. The results of this study provide a quantitative basis for decision-making in choosing the most effective security solution. The implementation of AHP proves to be efficient in resolving complex multi-criteria problems in the field of cloud security